(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Since the most important factor in activating the student’s creative thinking is live observation and abstract thinking, its development is considered the main issue. They were combined with the important qualities of the student’s personality, such as activity, independence, initiative, creative approach to work, and curiosity, which can meet the tasks of forming the student’s personality in education. In this article, there are given main information about methods of developing creative thinking skills of students in technology classes.